Dynamic assessment of language disabilities. (January 2015) - Martin, Deirdre
<x content-type="archive" xml:space="preserve">Abstract</x> The paper reports a study of a narrative-based Dynamic Assessment (DA) procedure developed in the USA that is used in the UK with children with developmental language disabilities. Three monolingual English children with language disabilities are assessed by a speech/language pathologist/therapist who is learning to work with DA in collaboration with the researcher in the study. Quantitative evidence of language structures indicates that the children learn to talk more after two intervention sessions. Evidence from the mediations of the children's language learning capabilities throws diagnostic light on the nature of their needs. A critique is offered of the assessment tool, and conclusions are drawn about the implications of DA for differentiating language-learning potential in language disabilities, with suggestions for further study.